An ethical and prudential argument for prioritizing the reduction of parasite-stress in the allocation of health care resources. - Powell, R; Clarke, S; Savulescu, J (Cambridge University Press, 2012)
The link between parasite-stress and complex psychological dispositions implies that the social, political, and economic benefits likely to flow from public health interventions that reduce rates of non-zoonotic infectious disease are far greater than have traditionally been thought. We sketch a prudential and ethical argument for increasing public health resources globally and redistributing these to focus on the alleviation of parasite-stress in human populations.